The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11695-016-2312-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cognitive Function Following Bariatric Surgery: a Systematic Review

Abstract: Increased body mass is directly associated with reduced cognitive function. The aim of this study was to systematically review the effect of bariatric weight loss surgery on cognitive function. A comprehensive and unrestricted literature search was conducted using the following databases: MEDLINE, EMBASE, PubMed, Scopus, Web of Sciences, and the Cochrane Library. A total of 414 publications were identified, of which 18 were included in the final review. Cognitive function as measured by a number of different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 68 publications
2
52
1
1
Order By: Relevance
“…In the present study, we did not find any substantial improvement in cognitive functions (primary and secondary outcomes) in patients of the BARS as compared to the NBARS group. This result was surprising in light of previous studies demonstrating the beneficial effects of weight loss after BARS on cognitive performance [19,20]. The only indication that BARS might have a beneficial Surgery groups, however, did not differ substantially with regard to changes in cognitive functions, mood/affect, and health-related quality of life.…”
Section: Effects Of Bars On Cognitive Functionscontrasting
confidence: 63%
See 1 more Smart Citation
“…In the present study, we did not find any substantial improvement in cognitive functions (primary and secondary outcomes) in patients of the BARS as compared to the NBARS group. This result was surprising in light of previous studies demonstrating the beneficial effects of weight loss after BARS on cognitive performance [19,20]. The only indication that BARS might have a beneficial Surgery groups, however, did not differ substantially with regard to changes in cognitive functions, mood/affect, and health-related quality of life.…”
Section: Effects Of Bars On Cognitive Functionscontrasting
confidence: 63%
“…In addition to weight loss and recovery from obesity-related diseases, a number of studies showed improved cognitive function after BARS (e.g., References [13][14][15][16]). Although most studies documented improvement in at least one neurocognitive domain, such as executive functions, memory, or attention, they were not unequivocal and consistent (for reviews, see References [17][18][19][20]). Georgiadou et al [21], for instance, was unable to find any substantial differences in cognitive assessments comparing 50 post-RYGB patients to a well-matched sample of patients seeking BARS.…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, Haltia et al (14) reported that cerebral white matter was more related to visceral fat accumulation, a marker of metabolic dysfunction, rather than total body fat mass. Together, these findings raise the possibility that changes in inflammation and metabolic factors following bariatric surgery improve WM structure and integrity, which may contribute, in part, to the improvement in cognitive functions observed after surgery-induced weight loss (26,27).…”
Section: Discussionmentioning
confidence: 93%
“…Bariatric surgery represents an interesting approach to address these questions, since it allows the examination of the effects of sustained weight loss and long-term metabolic improvements on the brain in a longitudinal setting (23)(24)(25). Growing evidence shows improvement in cognitive functions after bariatric surgery (26,27). However, only few structural MRI studies examined changes in GM and WM densities after bariatric surgery (9,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery has emerged as the most effective procedure to achieve rapid, significant and long-lasting weight reduction in individuals with moderate to extreme obesity (Maciejewski et al, 2016;O'Brien, MacDonald, Anderson, Brennan, & Brown, 2013;Padwal et al, 2011;Sjöström et al, 2004). Longitudinal studies have documented that weight loss induced by the surgery produces rapid and significant cognitive improvements (for reviews Handley, Williams, Caplin, Stephens, & Barry, 2016;Spitznagel et al, 2015;Veronese et al, 2017). Furthermore, improvements in executive functioning persist for at least 3 years after surgery .…”
Section: Introductionmentioning
confidence: 99%